2018
DOI: 10.1002/ijgo.12625
|View full text |Cite
|
Sign up to set email alerts
|

Childbirth experiences related to obstetric violence in public health units in Quito, Ecuador

Abstract: Various forms of obstetric violence are occurring in the public health services of Quito, despite World Health Organization recognition of the need for perinatal care at the highest level. Programs designed to prevent and diminish obstetric violence are urgently required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 10 publications
1
24
0
4
Order By: Relevance
“…Where episiotomy and Kristeller are concerned, more than one‐third of the women indicated that information was not given to them before the procedure was performed. These data have already been explored in an earlier paper, when describing the omission of the right to information …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where episiotomy and Kristeller are concerned, more than one‐third of the women indicated that information was not given to them before the procedure was performed. These data have already been explored in an earlier paper, when describing the omission of the right to information …”
Section: Resultsmentioning
confidence: 99%
“…The present study is part of a larger one, in which several criteria of obstetric violence were identified. The larger study investigates the postpartum experiences of women from units of the Ministry of Health of Ecuador, between the years 2016 and 2017, using a descriptive cross‐sectional design with a quantitative and qualitative approach …”
Section: Methodsmentioning
confidence: 99%
“…This support is reflected in the breastfeeding rates shown for the various SACs, where La Rioja had a similar breastfeeding starting rate to the other SACs, but presented a much higher breastfeeding percentage at six months than other communities [ 43 ]. The international literature has also related the presence of OV with little received support to commence breastfeeding [ 44 ]. Indeed mistreatment, abuse and OV are found to influence women’s decision making and their capacity to breastfeed their babies.…”
Section: Discussionmentioning
confidence: 99%
“…Women's own accounts of childbirth, available in the literature, often describe different obstetric interventions related to OV, such as not being accompanied by anyone, performing unnecessary cesarean sections, routine vaginal palpations, use of oxytocin, or performing the Kristeller maneuver, among other interventions [6][7][8] that are neither recommended nor backed by scientific evidence. Some studies also indicate a lack of respect and a higher level of intervention from the health professional's point of view [9].…”
Section: Introductionmentioning
confidence: 99%